2007
DOI: 10.1007/s11414-007-9054-6
|View full text |Cite
|
Sign up to set email alerts
|

Grounded Theory and Backward Mapping: Exploring the Implementation Context for Wraparound

Abstract: Within children's mental health, there is an increasing demand for wider implementation of wraparound and other interventions that can provide comprehensive, individualized, family-driven care. Unfortunately, implementation has proven difficult because these approaches do not necessarily flourish within traditionally organized agencies and systems. This has highlighted the need for information about how mental health agencies and systems must evolve if they are to provide a hospitable implementation environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Fidelity measures demonstrate a critical link between the wraparound process and outcomes (Bruns et al 2005) and may help explore what wraparound activities and principles are necessary and sufficient, similar to modular approaches in psychotherapy (Chorpita et al 2005b). In addition, organizational and system-level factors (e.g., funding, case load size, professional development) are hypothesized to affect the quality of the wraparound process (Walker and Koroloff 2007) and represent a new area of empirical research (Bruns et al 2006a, b). A logical comparison study could explore the differences between wraparound initiatives supported by systems of care (e.g., Wraparound Milwaukee, Kamradt et al 2005; the Dawn Project, Anderson et al 2008) and stand-alone wraparound programs.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Fidelity measures demonstrate a critical link between the wraparound process and outcomes (Bruns et al 2005) and may help explore what wraparound activities and principles are necessary and sufficient, similar to modular approaches in psychotherapy (Chorpita et al 2005b). In addition, organizational and system-level factors (e.g., funding, case load size, professional development) are hypothesized to affect the quality of the wraparound process (Walker and Koroloff 2007) and represent a new area of empirical research (Bruns et al 2006a, b). A logical comparison study could explore the differences between wraparound initiatives supported by systems of care (e.g., Wraparound Milwaukee, Kamradt et al 2005; the Dawn Project, Anderson et al 2008) and stand-alone wraparound programs.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…In an exploratory study that examined associations between fidelity of intervention with program implementation components, highlighted the importance of organizational and systems supports such as maintaining low caseloads, providing ongoing model training and staff support, and establishing systems level collaboration to achieve high degrees of model adherence. Finally, in a qualitative study using grounded theory methods, Walker and Koroloff (2007) explored the implementation context for wraparound to identify organizational and system variables that must change to support the model.…”
Section: Organizational Context and Organizational Readinessmentioning
confidence: 99%
“…While there has been little empirical study of the approaches presented, all publications (n = 8) acknowledged the limitations of training to support model adherence. The use of more direct methods to support integration of training content into practice settings, and the use of data-informed methods for coaching or supervision were emphasized Castillo and Padilla 2007;Malysiak 1999, Malysiak-Bertram 2001Walker and Koroloff 2007). One study found a relationship between the provision of skill-based coaching and increases in measured implementation fidelity .…”
Section: Supervision or Coachingmentioning
confidence: 99%
“…Attendance of natural supports in CFST meetings: Natural supports are people and other resources accessible to the family through their social and community relationships (Walker & Koroloff, 2007). Including natural supports in team meetings reflects two System of Care emphases: The first is a 'competence' or 'strengths-based' paradigm, wherein the role of professionals is to help families build their own support systems to actualize their intrinsic strengths over time (Marsh, 1996).…”
Section: Rationale For Fidelity Measuresmentioning
confidence: 99%